2010
DOI: 10.1055/s-0030-1263169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Medication Adherence in a Cohort of Patients with Bipolar Disorder

Abstract: Psychotic symptoms, poor insight, cannabis abuse/dependence and work impairment are negatively related to medication adherence during maintenance therapy of bipolar disorder. Patients with these characteristics may need a different therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 48 publications
7
50
2
1
Order By: Relevance
“…Our findings are likely to reflect the difficulty of managing manic patients in outpatient care, and suggest the need for inpatient care to facilitate proper treatment, an implication further supported by the finding that mania among patients who were diagnosed with bipolar disorder in inpatient care did not predict less prescription fills of prophylactic drugs after discharge. In contrast, patients presenting with mixed state at bipolar disorder diagnosis had an increased likelihood of filling a mood-stabilizer or antipsychotic prescription, contradicting the results from a prior study on adherence in different affective states (Gonzalez-Pinto et al, 2010). The reasons for this discrepancy are not clear.…”
Section: Discussioncontrasting
confidence: 73%
“…Our findings are likely to reflect the difficulty of managing manic patients in outpatient care, and suggest the need for inpatient care to facilitate proper treatment, an implication further supported by the finding that mania among patients who were diagnosed with bipolar disorder in inpatient care did not predict less prescription fills of prophylactic drugs after discharge. In contrast, patients presenting with mixed state at bipolar disorder diagnosis had an increased likelihood of filling a mood-stabilizer or antipsychotic prescription, contradicting the results from a prior study on adherence in different affective states (Gonzalez-Pinto et al, 2010). The reasons for this discrepancy are not clear.…”
Section: Discussioncontrasting
confidence: 73%
“…New data provide further insight into adherence to maintenance therapy in patients with BD. In several analyses, adherence was positively associated with higher satisfaction with medication, monotherapy, a college degree, and fear of relapse, and was negatively associated with illness factors (substance use, previous hospitalization, psychotic symptoms, reduced insight into illness), medication factors (side effects, no perceived daily benefit, difficulties with medication routines), and patient attitudes (belief that medications are unnecessary, negative attitudes toward medications, perceived change in appearance, perceived interference with life goals) (133)(134)(135)(136)(137)(138)(139). Under-dosing can also lead to higher discontinuation rates; patients receiving lower doses of ziprasidone had significantly higher discontinuation rates than those receiving medium or high doses (140).…”
Section: Clinical Questions and Controversiesmentioning
confidence: 99%
“…Rosa et al (42) reported in their study that 85.6% of their patients with bipolar disorder were compliant with lithium treatment. GonzalezPinto et al (43) started to follow up 1831 patients in the first 12 weeks of treatment and continued for 24 months, and they showed that 76.6% were treatment compliant, but 23.4% were treatment incompliant. Study results and the literature findings were different from each other, because methods to evaluate compliance were different, sample size contained patients with additional psychiatric diagnosis, sample size, follow-up duration for patient compliance, there were ethnically different groups, and differences between healthcare politics of the studies performed.…”
Section: Discussionmentioning
confidence: 99%